The degree to which financial culture teachers in Ajloun Governorate possess scientific research skills - Ahmad, Rwida Mohammad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree to which financial culture teachers in Ajloun governorate possess scientific research skills. The study adopted the descriptive analytical approach, and the study population consisted of (124) male and female teachers, and the study sample consisted of (66) male and female teachers, who were chosen randomly. The results of the study showed that the degree to which financial education teachers in public schools in Ajloun governorate possessed scientific research skills came at a high level, with an arithmetic mean (3.70), The study also revealed that there were no statistically significant differences to the degree to which teachers possessed scientific research skills according to the variable of job experience. Postgraduate category, the study recommended holding workshops for teachers; In order to get acquainted with how to write scientific research, and to train teachers on the use of writing and publishing scientific research, and to make the publication of research a condition of appointment.
Keywords: financial culture teachers; scientific research; Ajloun Governorate